Control financiero en la Comercializadora Agrícola Joflosa de la ciudad de Montalvo provincia de Los Ríos en el período 2020-2021. - Castillo Puya, Eddy Bryan (2022)
Agrícola JOFLOSA S.A. is a company dedicated to the wholesale sale and purchase of grains and seeds. To obtain financial information, a meeting was held with the legal representative to determine the investigative method in which observational techniques were applied. Which pointed out that, in 2020, despite the pandemic that the country experienced, they obtained favorable results, while in 2021 there was a reduction in their profits, for the period 2020 the Comercializadora Agrícola Joflosa SA, obtained a net profit of $709,692 .17, compared to the period of 2021 with a net profit of $74,120.63. The financial information of the marketer is detailed throughout this case study in which it can be verified that there is a variation in its net profit for the 2021 period, as observed in table 1, as well as the increase in the costs and expenses in 2021, an increase that affected net income. The problem of this case study is the lack of solvency or liquidity to meet financial obligations, increasing costs, expenses and reducing income, which leads to poor management of financial control, resulting in a decrease in Trader's profits. The line of research will be through the financial, tax and social commitment management subline, with the aim of publicizing the financial control of the marketer.